JOB SATISFACTION AS A MEDIATION VARIABLES ON THE EFFECT OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE PERFORMANCE - Fatmah Bagis; Utomo Indra Kusumo; Arini Hidayah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to find out the effect of organizational culture, organizational commitment on employee performance with job satisfaction as an intervening variables at PT Bank Syariah Mandiri Jakarta Head Office. The population in this research were all employees of PT Bank Syariah Mandiri Jakarta Head Office before merger to PT Bank Syariah Indonesia, as many as 150 employees, the sampling in this research used nonprobability sampling method with Incidental Sampling technique with the number sample were 100 respondents. Data obtained from respondents with a research instrument using a questionnaire. The analysis technique in this research used Partial Least Square (PLS) analysis Based on the research results, it shows the acceptance of the first hypothesis that organizational culture variables have a significant positive effect on employee performance. The results of the study show the rejection of the second hypothesis that the variable organizational commitment has a negative effect on employee performance. The research shows the results of the acceptance of the third hypothesis that organizational culture variables have a significant positive effect on job satisfaction. The results showed that the fourth hypothesis was not accepted that the variable organizational commitment had a significant negative effect on job satisfaction. The results showed that the fifth hypothesis was not accepted that the job satisfaction variable had no effect on employee performance. The research results, it can be concluded that job satisfaction cannot mediate the influence of organizational culture on employee performance. The result also showed that job satisfaction cannot mediate the relationship between organizational commitment and employee performance. Keywords: Organizational Culture, Organizational Commitment, Job Satisfaction, Employees Performance.